Oncofertility and Fertility Preservation in Cancer Patients Across the Twitterverse - Martinez-Ibarra, Nayeli A.; Remolina-Bonilla, Yuly A.; Buerba-Vieregge, Hector H.; Barragan-Carrillo, Regina; Castro-Alonso, Francisco J.; Mateos-Corella, Samantha; Bourlon, Maria T. (Frontiers in Endocrinology, 2022)
Purpose Infertility is a major problem affecting children, adolescents, and young adults (AYAs) with cancer, either due to the disease itself or because of oncologic treatment. Oncofertility (OF) focuses on counseling cancer patients about fertility risks and preservation options. However, OF and fertility preservation (FP) conversations on Twitter and their impact are unknown. We aim to characterize the users and type of content of these conversations. Materials and Methods This observational study analyzed tweets with the hashtags "#Oncofertility" and "#FertilityPreservation" over eight months. We classified Twitter accounts by user type and country. Tweets were categorized by content type, and retweets and likes were quantified. Descriptive statistics were used for analysis. Results A total of 399 tweets from 223 different accounts were evaluated. Twitter accounts comprised 22 countries and stems from high, upper-middle, and lower-middle-income countries in 86.5%, 5.4%, and 6.3%, respectively; no accounts from low-income countries were found. Accounts were mostly from physicians (37%) and healthcare centers (20%); we did not find any patient accounts. The most common content category was informative tweets directed to patients (30.8%), followed by discussion/sharing of medical papers (25.6%). Only 14.5% of tweets contained information about children and adolescents. Still, only 4.5% were aimed at them. Retweets were absent in 16.5% of the tweets, and 80.7% did not have comments. Conclusion OF and FP discussions on Twitter were limited to interactions among medical professionals. Also, advocacy groups showed limited activity on social media. Even though a significant proportion of tweets directed to patients were found, no active involvement of patients was observed. Finally, limited number of tweets (4.5%) were directed to children and adolescents. There is a need to raise awareness about the effects of cancer on fertility in this group. Currently, Twitter is not a resource of information for children and AYAs with cancer who need OF counseling and fertility preservation. Our results open a debate on how to promote the use of social media in the future to improve the quality of OF information available, awareness, and care since there is an unmet need for fertility preservation access in young cancer patients. .